1992
DOI: 10.1038/clpt.1992.84
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-pharmacodynamic modeling of the central nervous system effects of midazolam and its main metabolite α-hydroxymidazolam in healthy volunteers

Abstract: The pharmacodynamics of midazolam and its main metabolite alpha-hydroxymidazolam were characterized in individual subjects by use of saccadic eye movement and electroencephalographic (EEG) effect measurements. Eight healthy volunteers received 0.1 mg/kg midazolam intravenously in 15 minutes, 0.15 mg/kg alpha-hydroxymidazolam intravenously in 15 minutes, 7.5 mg midazolam orally and placebo in a randomized, double-blind, four-way crossover experiment. Plasma concentrations of midazolam, alpha-hydroxymidazolam an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
135
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(153 citation statements)
references
References 8 publications
11
135
3
Order By: Relevance
“…However, di erences in metabolic pathways between the two species, rat and man, and the interference of di erent (inter)active metabolites must be considered too. In contrast to the rat, in man metabolites of midazolam were found to contribute to the pharmacological e ects of the drug (Crevoisier et al, 1983;Mandema et al, 1992d). It has been suggested that the apparent acute tolerance to the actions of diazepam in man is due to redistribution of the compound from the central nervous system to the peripheral tissues (Greenblatt & Shader, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…However, di erences in metabolic pathways between the two species, rat and man, and the interference of di erent (inter)active metabolites must be considered too. In contrast to the rat, in man metabolites of midazolam were found to contribute to the pharmacological e ects of the drug (Crevoisier et al, 1983;Mandema et al, 1992d). It has been suggested that the apparent acute tolerance to the actions of diazepam in man is due to redistribution of the compound from the central nervous system to the peripheral tissues (Greenblatt & Shader, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, a large investigation is currently in progress on data obtained in some 150 rats where population analysis is used to identify factors that may be important in this respect. Similar studies are indicated in man and it is of interest that the EEG parameter utilized can also be applied in human studies (Mandema et al, 1992).…”
mentioning
confidence: 89%
“…On the other hand; glucuronidated α-hydroxymidazolam, the main metabolite of midazolam, has a substantial pharmacological effect and can penetrate the intact blood-brain barrier. The elimination half-time of α-hydroxymidazolam is about 70 min [25]. However, it can accumulate in patients with renal failure.…”
Section: Midazolammentioning
confidence: 99%
“…The α-hydroxymidazolam is as potent as the parent compound and may contribute significantly to the effects of the parent drug when present in sufficiently high concentrations. 4-Hydroxymidazolam is quantitatively unimportant [25]. Both metabolites are rapidly conjugated by glucuronic acid to form products which have been considered to be pharmacologically inactive [14].…”
Section: Midazolammentioning
confidence: 99%